BIBLIOMETRIC MAPPING OF ECONOMIC EDUCATION: BRADFORD’S LAW, CO-OCCURRENCE NETWORK ANALYSIS, AND THEMATIC MAPPING - Martha, Jefry Aulia; Wardoyo, Cipto; Hermawan, Agus (Nusantara Economics and Entrepreneurships Journals, 2025)
Economic education, as one of the fields of study in higher education, plays a crucial role in preparing the younger generation to understand and manage economic decisions. Research in this field has been growing rapidly, yet the direction of research needs to be well-mapped to identify future gaps. This study employs bibliometric techniques, including Bradford’s Law, Co-occurrence Network Analysis, and Thematic Mapping. The results reveal that the distribution of publications in this field is highly uneven. Bradford’s Law analysis shows that most publications come from a small number of key journals, while co-occurrence analysis identifies strong connections between various themes in economic education, with "economic education" as a central node linking major topics such as educational models, cognitive challenges, economic literacy, and entrepreneurship. This study indicates that economic education is interdisciplinary, encompassing cognitive, social, and behavioral dimensions. It suggests that more research should focus on integrating economic education theory with practical applications in areas such as entrepreneurship development and economic literacy. Furthermore, further exploration of the impact of evidence-based economic education interventions on student learning outcomes is recommended, along with identifying new opportunities for the development of curricula and economic education models that are more relevant to future needs.